2020
DOI: 10.3390/en13246549
|View full text |Cite
|
Sign up to set email alerts
|

Research on an Enterprise Remanufacturing Strategy Based on Government Intervention

Abstract: Due to rapid economic development and population growth, environmental pollution problems such as urban pollution and depletion of natural resources have become increasingly prominent. Municipal solid waste is part of these problems. However, waste is actually an improperly placed resource. As a part of green supply chain management, remanufacturing can turn waste products into remanufactured products for resale. Based on the development status of China’s remanufacturing industry, this paper establishes three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(37 reference statements)
0
2
0
1
Order By: Relevance
“…This emphasises the importance of close collaboration among various ELV stakeholders to achieve a win–win situation in business profit sharing and improve the ELV recovery. Cao et al (2020) indicated that government regulations and policy enforcement is crucial when the remanufacturing sector is in its early stages of establishment. Government regulations should serve as guidance to enhance public awareness of ELV treatment and encourage vehicle owners to send their ELV for recycling or remanufacturing voluntarily by providing subsidies.…”
Section: Resultsmentioning
confidence: 99%
“…This emphasises the importance of close collaboration among various ELV stakeholders to achieve a win–win situation in business profit sharing and improve the ELV recovery. Cao et al (2020) indicated that government regulations and policy enforcement is crucial when the remanufacturing sector is in its early stages of establishment. Government regulations should serve as guidance to enhance public awareness of ELV treatment and encourage vehicle owners to send their ELV for recycling or remanufacturing voluntarily by providing subsidies.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, referring to the index system introduced above. On the other hand, combining the particularity of the HCUA and the results of references [39][40][41][42] , the indicator system of GDI includes four dimensions: urban green construction (UGC), industrial green development (IGD), resource and environmental carrying capacity (RECC), and technological innovation support (TIS).…”
Section: Construction Of Indicator System Of Gdimentioning
confidence: 99%
“…Muitas ferramentas e conceitos foram apresentados como um meio para atingir tal intenção, sendo uma delas a Green Supply Chain Management (GSCM), podendo ser traduzida como Gestão Verde da Cadeia de Suprimentos. A importância da GSCM nesse contexto está, segundo Cao et al (2020), relacionada a ganhar e manter a vantagem competitiva corporativa, melhorar o desempenho e integrar os processos de GSCM com a gestão verde de recursos humanos.…”
Section: Introductionunclassified